Formulation development and evaluation of in situ nasal gel of poorly water soluble drug using mixed solvency concept - Agrawal, Archana; RK, Maheshwari (Asian Journal of Pharmaceutics (AJP), 2014)
The present study was aimed to develop a mucoadhesive in situ nasal gel containing domperidone with enhanced drug loading and transnasal permeation properties, which were achieved by improving drug solubility using the concept of mixed solvency. Poloxamer 407 was used as thermosensitive polymer and carbopol 934P as mucoadhesive polymer. Initially solubility of domperidone was enhanced in aqueous solution by using various solubilizers like sodium citrate (SC), urea (UR), polyvinyl pyrrolidone (PVP), polyethylene glycol (PEG), propylene glycol (PG) etc, individually and as a combination of two, three, and four solvents, respectively. Maximum solubility of domperidone was achieved at 30% w/w solvent concentration, containing mixed blend of PVP K30 (7.5% w/w) + PEG 400 (7.5% w/w) + PEG 600 (7.5% w/w) + Propylene Glycol (7.5% w/w), enhancing solubility of domperidone by 172.20 times as compared to its solubility in water. In situ gel was prepared by cold technique. Evaluation of the prepared gel was carried out, including properties like phase transition temperature, viscosity, in vitro drug release, drug content, transnasal permeation and stability studies. In vitro drug release studies of aqueous solution of mixed blend were performed and permeability coefficient was found to be 1.576 × 10-02 cm/hr and flux was found to be 8.64 μg/cm2hr. Similarly in vitro studies for in situ nasal gel were performed and percent cumulative drug release was 73.05±0.57% in 6 h.Transnasal drug permeation studies results in flux value of 7.04 μg/cm2hr and percent cumulative drug permeated across the membrane as 86.62±0.992%.The results from stability studies revealed that the prepared thermogel showed no significant decrease in drug content and no physicochemical change was observed upon storage in different temperature conditions resulting as a stable formulation.